Strategi E-marketing Dan Kualitas Website Melalui Online Customer Review Dan Implikasinya Terhadap Keputusan Pembelian Pada Marketplace Shopee Di Karawang - Danu Ruenda; Danang Kusnanto (Jurnal Ilmiah Wahana Pendidikan, 2023)
Digitalization contributes to a changing lifestyle as a result of society's increasing needs, resulting in a change in shopping patterns from cash to online. Consumers are influenced by many aspects when deciding to transact, including e-marketing strategies, website quality, and reviews written by consumers in e-commerce. Analyzing e-marketing strategies and website quality through Online Customer Reviews and their implications for purchasing decisions by focusing on the Shopee marketplace in Karawang is the purpose of this paper. This research is quantitative, with data processed using path analysis. The sample of respondents was selected using purposive sampling method and collected using a questionnaire. People in Karawang who have used Shopee were used as samples. The calculation results show that the E-marketing Strategy has an effect on Online Customer Review (0.000 <0.05). Then the Purchasing Decision on the Shopee marketplace in Karawang is influenced by the Online Customer Review (0.017 <0.05). Translated with www.DeepL.com/Translator (free version)